FAKTOR YANG BERHUBUNGAN DENGAN BAYI BERAT LAHIR RENDAH (BBLR) DI RUMAH SAKIT UMUM SAWERIGADING PALOPO - Marlina, Marlina; devianti, Devianti; Fitriana, Fitriana Ibrahim (Bina Generasi : Jurnal Kesehatan, 2024)
Low Birth Weight (LBW) is one of the health problems experienced by the community, which is marked with a birth weight less than 2500 grams. Low Birth Weight are basically related to the lack of nutrition during pregnancy, but there are still some nutritional factors, in this case the mother's age, parity, and education, and not only that, there are many more factors that can cause the LBW. Design research study is a descriptive cross sectional study with a sample of 22 people, who use the test perarson chi - square in SPSS 23. The purpose of this study is to know and identify factors associated with Low Birth Weight at Hospital General Sawerigading Palopo.based on stastiscal test found no association between Low Birth Weight with maternal age, parity, and education Where to maternal age obtained p-value = 0.003 with Low Birth Weight, for parity obtained p value = 0.001 with significance level α = 0.05, which means that there is a relationship between parity with Low Birth Weight, while the value obtained for educational p = 0.000 with significance level α = 0.05, which means that there is a relationship between education and Infant Birth Weight low. Conclusion there is a relationship between low birth weight infant(LBW) with maternal age, parity. Sebmitted suggestions notice and researchers in order to improve health care, especially during pregnancy and frequent checkups on the health of health care workers so that the baby can be improved. Keywords : Low birth Weight, Maternal Age, Parity